The environmental car and its opposites - a brief history of car emission debates and regulations in Sweden 1986-2007 - Hagman, Olle; Pedersen, Martin Bae (Proceedings from the Annual Transport Conference at Aalborg University, 2008)
In this paper we present an historical overview of the two car types starting with the ECV and moving on to the city jeeps. The histories will differ because there are different actors driving them. We end with a critical discussion where we try to sum up this discourse in historical, environmental and social terms. We ask the question; Are there parallels to be drawn between the development of the SUV and the ECV? Is there anything to be learned from the history of the SUV that could help detecting inbuilt antagonisms within the ECV concept that points to future problem areas and declining sales also in this segment?